2003
DOI: 10.1590/s0102-695x2003000400013
|View full text |Cite
|
Sign up to set email alerts
|

Flavonóides isolados do pólen coletado pela abelha Scaptotrigona bipunctata (canudo)

Abstract: __________________________________________________________________ ResumoPólen de abelhas é uma mistura de pólens florais coletados pelas abelhas com ampla variação na sua composição. Investigação do pólen coletado pela abelha sem ferrão Scaptotrigona bipunctata levou a quatro agliconas de flavonóides: miricetina, dihidromiricetina, quercetina e isoramnetina. As estruturas foram estabelecidas a partir de dados espectroscópicos (NMR) das substâncias naturais. AbstractBee pollen is a mix of bee-collected floral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Taxifolin ( 2 ), isoquercetin (Isoq, 3 ), myricetin (Myri, 4 ), tricetin (Tri, 5 ), naringenin ( 6 ), quercetin (Quer, 7 ), luteolin (Lut, 8 ), selagin (Sel, 9 ), kaempferol (Kae, 10 ), and isorhamnetin (Isor, 11 ), were previously isolated and identified from pollen loads [ 6 , 7 , 8 ]. Folin-Ciocalteu’s phenol reagent, 1,1-diphenyl-2-picryl hydrazyl (DPPH), potassium persulfate, 6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid (Trolox), beta-carotene, linoleic acid and ferrozine were obtained from Sigma-Aldrich (Sternheim, Germany), and butylated hydroxytoluene (BHT) was supplied by Acros Organics (New Jersey, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taxifolin ( 2 ), isoquercetin (Isoq, 3 ), myricetin (Myri, 4 ), tricetin (Tri, 5 ), naringenin ( 6 ), quercetin (Quer, 7 ), luteolin (Lut, 8 ), selagin (Sel, 9 ), kaempferol (Kae, 10 ), and isorhamnetin (Isor, 11 ), were previously isolated and identified from pollen loads [ 6 , 7 , 8 ]. Folin-Ciocalteu’s phenol reagent, 1,1-diphenyl-2-picryl hydrazyl (DPPH), potassium persulfate, 6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid (Trolox), beta-carotene, linoleic acid and ferrozine were obtained from Sigma-Aldrich (Sternheim, Germany), and butylated hydroxytoluene (BHT) was supplied by Acros Organics (New Jersey, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In our continuing search for bee-pollen products [ 6 , 7 , 8 ], we have studied the palynological origin, phenolic content, flavonoid content, and antioxidant properties of twenty-five samples of bee pollen harvested from the Canavieiras municipality (northeastern Brazil) during a nine-month period (February–November).…”
Section: Introductionmentioning
confidence: 99%
“…The few accounts found are those of Wollenweber and Wiermann (1979) who reported the presence of the free chalcone aglycone, and Strohl and Seikel (1965) who found dihydroflavonols. More recently Campos et al (1997Campos et al ( , 2002 and Lins et al (2003) reported the presence of flavones and flavonols. It is of interest therefore that all flavonoids found here in pollen loads of M. subnitida are aglycones.…”
Section: Determination Of Isolated Compoundsmentioning
confidence: 99%
“…It is of interest therefore that all flavonoids found here in pollen loads of M. subnitida are aglycones. Furthermore, selagin is reported as a pollen constituent for the first time and the flavonoids: tricetin (Campos et al, 2002;Campos et al, 1997), isorhamnetin (Lins et al, 2003;Tomas-Lorente et al, 1992), 8-methoxyherbacetin (Campos, 1997;Dauguet et al, 1993), and naringenin (Strohl and Seikel, 1965) have been isolated previously from pollen loads. This is however the first report of D-mannitol as a constituent of pollen loads with a substantial proportion (34.9%).…”
Section: Determination Of Isolated Compoundsmentioning
confidence: 99%
“…The next sample was injected after 15 min. The genuine standards of flavonoids were acquired as follows: myricetin (Acros Organics), kampferol (Sigma-Aldrich) and taxifolin, isoquercetin, tricetin, naringenin, quercetin, luteolin, selagin and isoramnetin were previously isolated from pollen loads studied in our laboratory (Lins et al, 2003;Silva et al, 2006). The chromatogram of phenolic extract ( Fig.…”
Section: Bee Polen Phenolic Extract Preparationmentioning
confidence: 99%